Exploring Readiness Toward the Implementation of Blended Learning Among Lecturers and Students of Foreign Languages - Ribahan Ribahan (Departement of Mathematics Education, 2023)
This study aimed to explore the availability of facilities to implement blended learning in teaching and learning foreign languages, the use of the internet and e-learning literacy among lecturers and students of foreign languages departments, and the readiness for blended learning in teaching and learning foreign languages. This study used a mixed method which combined quantitative and qualitative descriptive methods. A questionnaire containing several statements was distributed to lecturers and students of the English and Arabic Departments ​​to collect necessary data. The statements break down into three categories according to the problems in this study. The first are the ones that require close answers yes or no, while the second and third are the ones that demand responses on four scales namely strongly disagree, disagree, agree, and strongly agree. Then, the data were analyzed using descriptive statistics. The results of the study revealed that the lecturers and students had the needed facilities to support the implementation of blended learning, yet the internet service in terms of coverage and accessibility at the campus was not adequate. It was also known that the lecturers and the students had the knowledge and skills to operate any tools and features of the internet for blended learning. Most importantly, the lecturers and students were ready for the implementation of blended learning in the teaching and learning of English and Arabic.